Left Retrosigmoid Craniotomy for Resection of Cavernous Malformation: 2-Dimensional Operative Video. Issue 1 (23rd November 2019) - Hendricks, Benjamin K; Spetzler, Robert F
Abstract: Pontine cavernous malformations are highly morbid lesions that require thorough preoperative planning of the surgical approach and meticulous surgical technique to successfully remove. The patient in this case has a large pontine cavernous malformation coming to the parenchymal surface along the pontine–middle cerebellar peduncle interface. The depth of the surgical field and narrow trajectory of approach require use of lighted suction, lighted bipolar forceps, and stereotactic neuronavigation to successfully locate and remove the entire lesion. The cavernous malformation is removed in a piecemeal manner with close inspection of the resection cavity for any remnants. Postoperative imaging demonstrates gross total resection of the lesion. The patient gave informed consent for surgery and video recording. Institutional review board approval was deemed unnecessary. Used with permission from Barrow Neurological Institute, Phoenix, Arizona .